Diagnosis and therapy of ascites in liver cirrhosis - Biecker, Erwin (Baishideng Publishing Group Co., Limited, 2011)
Ascites is one of the major complications of liver cirrhosis and is associated with a poor prognosis. It is important to distinguish noncirrhotic from cirrhotic causes of ascites to guide therapy in patients with noncirrhotic ascites. Mild to moderate ascites is treated by salt restriction and diuretic therapy. The diuretic of choice is spironolactone. A combination treatment with furosemide might be necessary in patients who do not respond to spironolactone alone. Tense ascites is treated by paracentesis, followed by albumin infusion and diuretic therapy. Treatment options for refractory ascites include repeated paracentesis and transjugular intrahepatic portosystemic shunt placement in patients with a preserved liver function. Potential complications of ascites are spontaneous bacterial peritonitis (SBP) and hepatorenal syndrome (HRS). SBP is diagnosed by an ascitic neutrophil count > 250 cells/mm(3) and is treated with antibiotics. Patients who survive a first episode of SBP or with a low protein concentration in the ascitic fluid require an antibiotic prophylaxis. The prognosis of untreated HRS type 1 is grave. Treatment consists of a combination of terlipressin and albumin. Hemodialysis might serve in selected patients as a bridging therapy to liver transplantation. Liver transplantation should be considered in all patients with ascites and liver cirrhosis.